The Relationship between Supervision on Nursing Care Done by the Head of Room and the Implementation of Standard Operational Procedure of Parenteral Drug Administration - Reska Handayani; Junaiti Sahar; Basmanelly . (Faculty of Nursing, Universitas Andalas, 2018)
Purpose: This research aims at discovering the relationship between nursing care supervision done by chief nurse and the implementation of Standard Operational Procedure of parenteral drug giving at RSUD Solok. Method: The research method is descriptive analytic with cross sectional design. It was done from July until August 2014 by using questionnaire and observation to 96 nurses in charge. The sample was taken by using proportional sampling from each in-patient room. The data were analyzed by using chi-square and logistic regression analysis. Result: The result shows that there was a correlation between Head of Room supervision, which includes planning with p value=0,004, implementation with p value=0,001, evaluation and feed back with p value=0,012 and documentation with p value= 0,037, towards the implementation of Standard Operational Procedure of parenteral drug administration. The dominant variable of the implementation of Standard Operational Procedure of parenteral drug is supervision, with p value = 0,001 and OR=4,14. Conclusion: From the result, it can be concluded that chief nurse supervision has a meaningful correlation towards the implementation of Standard Operational Procedure of parenteral drug.